Factors associated with the uptake of biosimilars for breast cancer treatment from the perspectives of physicians and patients-Evidence from China - Wu, Qiyou; Lian, Zhiwei; Wang, Xin; Cheng, Hanchao; Sun, Jing; Yu, Hui; Zhang, Gong; Wu, Fan; Liu, Jian; Chen, Chuanben (Frontiers in Pharmacology, 2023)
Objective: To investigate the factors associated with the treatment of breast cancer with biosimilars from the perspectives of physicians and patients, and to generate evidence for promoting the uptake of biosimilars. Methods: This study targeted trastuzumab and its indicated human epidermal growth factor receptor 2 (HER2) positive breast cancer and included female HER2 positive breast cancer patients under treatment of trastuzumab at a provincial oncology medical center in southern China from 1 January 2021, to 31 December 2021. The study extracted patients’ demographic, socioeconomic and clinical information and the basic information of their attending physicians from the hospital information system. We performed a bivariate multiple logistic regression analysis of predictive factors of the use of trastuzumab biosimilar. Results: A total of 446 patients (aged ranging between 26 and 74, 51.4 ± 9.06) were included in the analysis, and 19.1% chose biosimilar trastuzumab. Older patients, patients enrolled in the urban and rural resident health insurance program compared with those enrolled in the urban employee health insurance program, patients who initiated treatment after January 2021 when biosimilar entered clinical use compared with those who initiated treatment before, patients with female attending physicians, younger attending physicians and with chief attending physicians compared with deputy chief attending physicians were more likely to adopt biosimilar trastuzumab for treatment (p < 05). Controlling the other factors unchanged, when the patient’s attending physician was deputy chief physician, increasing 1 year age of the patient was associated with an increased probability of adopting biosimilar by .8% (dy/dx = .008, 95%CI: .002–.01, p = .01). When the patient was aged between 26 and 60, the probability of adopting biosimilar for the patient whose attending physician was a chief physician was higher than for those whose attending physician was a deputy chief physician, and the gap was the largest when the patient was at the age of 45 (dy/dx = .20, 95%CI: .13–.27, p < .01). Conclusion: The uptake rate of biosimilars is still low at its initial development stage in China. Educational policies and physicians making recommendations to the indicated patients at the initiation stage of treatment are helpful to avoid reduced willingness to switch to biosimilars due to non-clinical reasons. Patients with lower ability-to-pay will have better accessibility to biologic regimens through the uptake of biosimilars. Official guidelines and professional training are critical to enhancing physicians’ willingness and confidence in adopting biosimilars.